Pregnancy Outcomes in Patients With Multiple Sclerosis Exposed to Natalizumab—A Retrospective Analysis From the Austrian Multiple Sclerosis Treatment Registry - Guger, Michael; Traxler, Gerhard; Drabauer, Martina; Leitner-Pohn, Doris; Enzinger, Christian; Leutmezer, Fritz; Oel, Dierk; Di Pauli, Franziska; Berger, Thomas; Ransmayr, Gerhard (Frontiers in Neurology, 2020)
Objectives: To analyze safety and impact of natalizumab (NTZ) exposure on the disease course, pregnancy, and newborn outcomes of relapsing-remitting multiple sclerosis (RRMS) patients from the Austrian Multiple Sclerosis Treatment Registry (AMSTR). Materials and Methods: Twelve pregnancies of 11 women with RRMS exposed to treatment with NTZ were identified from the AMSTR. Exposure to NTZ was defined as treatment with NTZ from 8 weeks prior to the start of the last menstrual period and onward. All patients completed a standardized questionnaire regarding pregnancy and newborn outcomes until the postpartum period for up to 12 months. Results: NTZ was stopped on average 46 days after the last menstrual period. There were 11 live births and one elective termination due to ectopic pregnancy. Mean gestational age of live born individuals was 39.0 weeks [standard deviation (SD) ± 1.1]. Mean birth weight and length were 3,426 g (SD ± 348) and 51.9 cm (SD ± 1.9), respectively. Apgar scores 1 min after birth were normal, with 9.2 points on average. One child displayed hip dysplasia as the only congenital malformation documented in this cohort. Three patients experienced relapses during pregnancy and three patients in the postpartum period, resulting in confirmed Expanded Disability Status Scale (EDSS) progression in four of them. Conclusion: In this cohort, there was no increased risk concerning pregnancy and newborn outcomes due to NTZ exposure. However, relapses occurring during pregnancy and postpartum period resulted in confirmed disability.